Recent Advances in Metal Oxide and Phosphate Nanomaterials Radiolabeling with Medicinal Nuclides - Janská, Tereza; Sakmár, Michal; Štíbr, Matěj; Vlk, Martin; Kozempel, Ján (ACS omega, 2024)
The utilization of nanomaterials in biomedical applications has surged in recent years; yet, the transition from research to practical implementation remains a great challenge. However, a promising area of research has emerged with the integration of nanomaterials with diagnostic and therapeutic radionuclides. In this Review, we elucidate the motivations behind selecting metal oxide- and phosphate-based nanomaterials in conjunction with these radionuclides, while addressing its issues and limitations. Various metal oxide- and phosphate-based nanoparticles, exhibiting low toxicity and high tolerability, have been proposed for diverse biomedical applications, ranging from bone substitutes to drug delivery systems and controlled release vectors for pharmaceuticals, including radionuclides for nuclear medicine imaging and therapy. Moreover, the potential synergistic effects of multimodal combinational therapies, integrating chemotherapeutics, immunomodulators, or hyperthermia, underscore the versatility of these nanoconstructs. Our comprehensive exploration includes the underlying principles of radiolabeling strategies, the pivotal attributes of nanomaterial platforms, and their applications. Through this perspective, we present the potential of nanotechnology-enabled nuclear medicine. Furthermore, we discuss the potential systemic and local applications of these nanoconstructs, considering their in vitro and in vivo characteristics, as well as their physicochemical properties.